Retrieval of forest fuel moisture content using a coupled radiative transfer model. (September 2017) - Quan, Xingwen; He, Binbin; Yebra, Marta; Yin, Changming; Liao, Zhanmang; Li, Xing
Abstract: Forest fuel moisture content (FMC) dynamics are paramount to assessing the forest wildfire risk and its behavior. This variable can be retrieved from remotely sensed data using a radiative transfer model (RTM). However, previous studies generally treated the background of forest canopy as soil surface while ignored the fact that the soil may be covered by grass canopy. In this study, we focused on retrieving FMC of such forestry structure by coupling two RTMs: PROSAIL and PRO-GeoSail. The spectra of lower grass canopy were firstly simulated by the PROSAIL model, which was then coupled into the PRO-GeoSail model. The results showed that the accuracy level of retrieved FMC using this coupled model was better than that when the PRO-GeoSail model used alone. Further analysis revealed that low FMC condition fostered by fire weather condition had an important influence on the breakout of a fire during the study period. Highlights: We proposed a novel method to retrieve FMC of the two-layered forest canopy. The PROSAIL and PRO-GeoSail models were coupled to simulate the spectra of such forest structure. Ecological rules were used to alleviate the ill-posed inverse problem. The coupled model retrieved FMC performed better than PRO-GeoSail model alone.